Rhinosporidiosis in horses - Fernando F. Argenta; Lauren S. Mello; Andreia Vielmo; Saulo P. Pavarini; David Driemeier; Luciana Sonne (Pesquisa Veterinária Brasileira)
ABSTRACT: Rhinosporidiosis is a disease caused by Rhinosporidium seeberi, an aquatic protist of the class Mesomycetozoa. It primarily affects the nasal mucosa and transmission is associated with contaminated water contact. This report describes seven cases of rhinosporidiosis in horses in Rio Grande do Sul covering the period of 13 years. The disease predominantly affected Crioulo and thoroughbred horses. No apparent gender predisposition occurs, and age ranged from two to 25 years, with a median of 10 years. The gross aspects were characterized by unilateral (85.7%, 6/7) or bilateral (14.3%, 1/7) polyps. These were soft to friable, whitish to pink, cauliflower-like, with an irregular, sometimes ulcerated surface, measuring 2.5 to 6.0cm in diameter. There was a severe inflammatory infiltrate of the submucosa was observed, associated with moderate proliferation of the epithelium, and numerous rounded structures were identified compatible with sporangia of R. seeberi. Rhinosporidiosis should be included in the differential diagnosis of other conditions affecting the respiratory tract of horses, and it is important to perform histopathology for diagnosis.